Implementation of the Brainstorming Method to Improve Learning Activities of Fourth Grade Students of SD Negeri 0104 Sibuhuan - Rizki Hamdan Saputra; Darmatua Pasaribu; Era Mutiah (PT. Gyandharma Global Media, 2026)
The type of research used is classroom action research (CAR). This research was conducted in class IV of SD Negeri 0104 Sibuhuan. The subjects in the research were class IV of SD Negeri 0104 Sibuhuan. Based on the results of the study, it can be concluded that: (1) The learning activities of class IV students of SD Negeri 0104 Sibuhuan in the pre-cycle are still low. This can be seen from the results of observations that have been carried out, the average value of student learning activities is 62.63, student learning activities with the category